1974
DOI: 10.1039/p19740001611
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic studies. Part XXXI. New routes to reduced imidazole, pyrimidine, and pyridopyrimidine derivatives

Abstract: Treatment of 4-(substituted amino)-6-chloro-5-nitropyrimidines (4-substituents N-ethylanilino, hexamethyleneamino, Nmethyl -2hydroxyethylami no, 2hyd roxyethyla mi no, al lylami no, and benzy la mi no) with d iI Ute acetic acid gave corresponding 3-(substituted amino)-3-amino-2-nitroacrylonitrile derivatives. Cyclisation of 4-(N-alkyl-2chloroethylamino) -6-chloro-5-nitropyrimidines gave imidazopyrimidines which were immediately cleaved to give dihydroimidazoles with a 2-[cyano(nitro)methylene] substituent. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Earlier it was shown that such hydrolysis can occur in either acidic or alkaline or neutral media [62][63][64] and transform 4-chloro-5-nitropyrimidine derivatives 97 into highly polarized nitroenediamines 99 (Scheme 38). Acidic hydrolysis provides better yields.…”
Section: Reactions Resulting In Formation Of Acyclic Enamine Derivatimentioning
confidence: 99%
“…Earlier it was shown that such hydrolysis can occur in either acidic or alkaline or neutral media [62][63][64] and transform 4-chloro-5-nitropyrimidine derivatives 97 into highly polarized nitroenediamines 99 (Scheme 38). Acidic hydrolysis provides better yields.…”
Section: Reactions Resulting In Formation Of Acyclic Enamine Derivatimentioning
confidence: 99%
“…The starting 6-chloro-5-nitropyrimidines 1, 2 were synthesized according to the methods in [3,4]. Reaction of 4-Substituted 6-Chloro-5-nitropyrimidines (1, 2) with N-Benzylphenacylamine.…”
mentioning
confidence: 99%
“…The use of ammonium acetate as the catalyst leads to a side reaction involving closure of an isothiazole ring to give isothiazolo [5,4-d]pyrimidines. Thiocyanates 3a-d were obtained in high yield (Scheme 1).Since the lability of the chlorine atoms in 1a,b is less than in the analogous 5-nitropyrimidines, we were able to replace only one of the chlorine atoms by a thiocyanate group in 2-methylmercapto derivative 1b [7][8][9]. The synthetic methods for thiocyanate derivatives are based, as a rule, on the reaction of the corresponding halides, sulfates, or sulfonates with ammonium or alkali metal thiocyanates [3,4].…”
mentioning
confidence: 99%
“…Since the lability of the chlorine atoms in 1a,b is less than in the analogous 5-nitropyrimidines, we were able to replace only one of the chlorine atoms by a thiocyanate group in 2-methylmercapto derivative 1b [7][8][9]. The reaction was carried out in methanol at 17°C and monitored by thin-layer chromatography.…”
mentioning
confidence: 99%
See 1 more Smart Citation